Answer:
x = 3, y = 6
Step-by-step explanation:
In the figure attached,
If ΔADE and ΔABC are similar triangles, their corresponding sides will be in the same ratio.
By this property,
![\frac{AB}{AD}=\frac{AC}{AE}=\frac{BC}{DE}](https://tex.z-dn.net/?f=%5Cfrac%7BAB%7D%7BAD%7D%3D%5Cfrac%7BAC%7D%7BAE%7D%3D%5Cfrac%7BBC%7D%7BDE%7D)
![\frac{AB}{AD}=\frac{AC}{AE}](https://tex.z-dn.net/?f=%5Cfrac%7BAB%7D%7BAD%7D%3D%5Cfrac%7BAC%7D%7BAE%7D)
![\frac{AD+BD}{AD}=\frac{AE+EC}{AE}](https://tex.z-dn.net/?f=%5Cfrac%7BAD%2BBD%7D%7BAD%7D%3D%5Cfrac%7BAE%2BEC%7D%7BAE%7D)
![\frac{3}{2}=\frac{x+1.5}{x}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B2%7D%3D%5Cfrac%7Bx%2B1.5%7D%7Bx%7D)
3x = 2x + 3
3x - 2x = 3
x = 3
Similarly, ![\frac{AB}{AD}=\frac{BC}{DE}](https://tex.z-dn.net/?f=%5Cfrac%7BAB%7D%7BAD%7D%3D%5Cfrac%7BBC%7D%7BDE%7D)
![\frac{3}{2}=\frac{y}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B2%7D%3D%5Cfrac%7By%7D%7B4%7D)
y = ![\frac{3\times 4}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B3%5Ctimes%204%7D%7B2%7D)
y = 6
Answer:
113
Step-by-step explanation:
we need to know how much Lou has first !
so we have to do 682 / 6 which = 113
then 113 / 4 = 28.2
28.2 is how much Lou has
so we will go back and multiply the 4
28.2 x 4 =113
Answer:
two sets are said to be overlapping if they contain at least one element in common A=(1,2,3,4)and B =(4,7,1,9)are said to be overlapping sets.
Step-by-step explanation:
please answer my question I answer your question
(xii) NH₂ + Cl₂ →→→→NH₂CI+ N₂
(xiv) NaOH + Cl₂ →→ NaCl + NaCIO + H₂O
" (vi) CH, + 0,— CO, + H,0
xviii) C₂H₂ + O₂2 CO₂ + H₂O
(xx) Na + H₂O → NaOH + H₂
A (xxii) PbO₂ PbO + 0₂
xxiv) NH3 + CuO →→→ → N₂ + H₂O + Cu
xxvi) H₂S + Cl₂ →→→ HCI + S
xviii) H₂S + H₂SO4 → H₂O + SO₂ + S
(xxx) C + HNO3 → CO₂ + NO₂ + H₂O
Let's make an equation. T will be the number.
(T+5)/4=7
Let's multiply both sides by 4 to get T by itself.
T+5=28
Subtract 5 from both sides.
T=23
Your number is 23.
Answer:
![\left(\dfrac{2}{3},\dfrac{1}{5}\right)](https://tex.z-dn.net/?f=%5Cleft%28%5Cdfrac%7B2%7D%7B3%7D%2C%5Cdfrac%7B1%7D%7B5%7D%5Cright%29)
Step-by-step explanation:
Given the system of two equations:
![\left\{\begin{array}{l}\dfrac{1}{2}x-\dfrac{3}{4}y=\dfrac{11}{60}\\ \\\dfrac{2}{5}x+\dfrac{1}{6}y=\dfrac{3}{10}\end{array}\right.](https://tex.z-dn.net/?f=%5Cleft%5C%7B%5Cbegin%7Barray%7D%7Bl%7D%5Cdfrac%7B1%7D%7B2%7Dx-%5Cdfrac%7B3%7D%7B4%7Dy%3D%5Cdfrac%7B11%7D%7B60%7D%5C%5C%20%5C%5C%5Cdfrac%7B2%7D%7B5%7Dx%2B%5Cdfrac%7B1%7D%7B6%7Dy%3D%5Cdfrac%7B3%7D%7B10%7D%5Cend%7Barray%7D%5Cright.)
Multiply the first equation and the second equation by 60 to get rid of fractions:
![\left\{\begin{array}{l}30x-45y=11\\ \\24x+10y=18\end{array}\right.](https://tex.z-dn.net/?f=%5Cleft%5C%7B%5Cbegin%7Barray%7D%7Bl%7D30x-45y%3D11%5C%5C%20%5C%5C24x%2B10y%3D18%5Cend%7Barray%7D%5Cright.)
Now multiply the first equation by 4 and the second equation by 5:
![\left\{\begin{array}{l}120x-180y=44\\ \\120x+50y=90\end{array}\right.](https://tex.z-dn.net/?f=%5Cleft%5C%7B%5Cbegin%7Barray%7D%7Bl%7D120x-180y%3D44%5C%5C%20%5C%5C120x%2B50y%3D90%5Cend%7Barray%7D%5Cright.)
Subtract them:
![(120x-180y)-(120x+50y)=44-90\\ \\120x-180y-120x-50y=-46\\ \\-230y=-46\\ \\y=\dfrac{46}{230}=\dfrac{1}{5}](https://tex.z-dn.net/?f=%28120x-180y%29-%28120x%2B50y%29%3D44-90%5C%5C%20%5C%5C120x-180y-120x-50y%3D-46%5C%5C%20%5C%5C-230y%3D-46%5C%5C%20%5C%5Cy%3D%5Cdfrac%7B46%7D%7B230%7D%3D%5Cdfrac%7B1%7D%7B5%7D)
Substitute it into the first equation:
![30x-45\cdot \dfrac{1}{5}=11\\ \\30x-9=11\\ \\30x=11+9\\ \\30x=20\\ \\x=\dfrac{2}{3}](https://tex.z-dn.net/?f=30x-45%5Ccdot%20%5Cdfrac%7B1%7D%7B5%7D%3D11%5C%5C%20%5C%5C30x-9%3D11%5C%5C%20%5C%5C30x%3D11%2B9%5C%5C%20%5C%5C30x%3D20%5C%5C%20%5C%5Cx%3D%5Cdfrac%7B2%7D%7B3%7D)
The solution is